CARBOHYDRATES MALABSORPTION IN CLINICAL PRACTICE OF PEDIATRICS - Горобець, Анастасія; Прощенко, Юлія (SWorldJournal, 2025)
Food intolerance is one of the problems that pediatricians most often face in their practice. The main place in the structure of this pathology is occupied by malabsorption of carbohydrates - a group of diseases caused by impaired breakdown and / or abso